2023
DOI: 10.1093/mnras/stad3364
|View full text |Cite
|
Sign up to set email alerts
|

The first comprehensive study of a giant nebula around a radio-quiet quasar in the z < 1 Universe

Zhuoqi Liu,
Sean D Johnson,
Jennifer I-Hsiu Li
et al.

Abstract: We present the first comprehensive study of a giant, ≈70 kpc-scale nebula around a radio-quiet quasar at z < 1. The analysis is based on deep integral field spectroscopy with Multi-Unit Spectroscopic Explorer of the field of HE 0238−1904, a luminous quasar at z = 0.6282. The nebula emits strongly in [O ii], $\rm H \beta$, and [O iii], and the quasar resides in an unusually overdense environment for a radio-quiet system. The environment likely consists of two groups which may be merging, and in total hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 121 publications
1
9
0
Order By: Relevance
“…Finally, previous studies have identified a correlation between the presence of close companions around the QSOs and the presence of strong, extended nebular line emission (see, e.g., a narrowband imaging survey by Stockton & MacKenty 1987). In our sample, the morphokinematics of some nebulae (e.g., PKS0405−123, HE0238−1904, TXS0206−048) reveal that part of the line-emitting gas originates from stripped ISM of group member galaxies as indicated by consistent line-of-sight velocities between the galaxies and extended nebulae (see, e.g., Johnson et al 2018;Helton et al 2021;Liu et al 2024). It is natural to assume in these cases that the tidal interactions between group member galaxies disturb the gas and enhance the turbulence and thermal instabilities in the hot halo, leading to more efficient cooling and cool clump condensation.…”
Section: Implications For the Multiphase Cgm Dynamicsmentioning
confidence: 53%
See 2 more Smart Citations
“…Finally, previous studies have identified a correlation between the presence of close companions around the QSOs and the presence of strong, extended nebular line emission (see, e.g., a narrowband imaging survey by Stockton & MacKenty 1987). In our sample, the morphokinematics of some nebulae (e.g., PKS0405−123, HE0238−1904, TXS0206−048) reveal that part of the line-emitting gas originates from stripped ISM of group member galaxies as indicated by consistent line-of-sight velocities between the galaxies and extended nebulae (see, e.g., Johnson et al 2018;Helton et al 2021;Liu et al 2024). It is natural to assume in these cases that the tidal interactions between group member galaxies disturb the gas and enhance the turbulence and thermal instabilities in the hot halo, leading to more efficient cooling and cool clump condensation.…”
Section: Implications For the Multiphase Cgm Dynamicsmentioning
confidence: 53%
“…To gain further insights into the differences between these dynamical systems, we convert the estimated ò to a turbulent heating rate per unit volume via Q turb = ρò, where ρ is the gas density and can span a wide range for gas in different phases. For the QSO nebulae in our sample, the [O II] λλ3727,3729 doublet line ratios suggest a median upper limit of gas density for the T ∼ 10 4 K cool phase of 40 cm −3 (Liu et al 2024), while an estimate of ≈1-5 cm −3 is obtained assuming a pressure equilibrium between typical active galactic nucleus (AGN)illuminated [O II]-emitting gas and the hot halo (Johnson et al 2022). Based on the [S II]λλ6716, 6731 doublet ratio, observations of spatially extended nebula illuminated by the AGN in the Teacup galaxy at z ∼ 0.1 show that the gas density at distances of a few kiloparsec away from the galaxy center is 10 cm −3 (Venturi et al 2023).…”
Section: Energy Transfer Rate Over Seven Decades In Spatial Scalementioning
confidence: 77%
See 1 more Smart Citation
“…The broad spectral coverage (4700-9350 Å), wide field of view (1 1 ¢ ´¢), and high throughput (peaking at 35% at 7000 Å) of MUSE (Bacon et al 2010) collectively enable searches for low-surface-brightness nebulae in the environments of the CUBS and MUSEQuBES background quasars at z = 0.4-1.4 (Johnson et al 2018(Johnson et al , 2022M. C. Chen et al 2023;Liu et al 2024) at the same time. The MUSEQuBES MUSE observations (PI: J. Schaye) were conducted in the MUSE wide-field mode under natural seeing conditions characterized by a FWHM = 0 5-1 0 with 2 to 10 hr of integration.…”
Section: Observations Data Reduction and Processingmentioning
confidence: 99%
“…Recent IFS-enabled discoveries at lower redshifts of z < 1.5 revealed the potential for studies of ≈30-100 kpc-scale CGM nebulae observed in emission in nonresonant, rest-frame optical lines (e.g., [O II], Hβ, and [O III]) and resonant near-UV (NUV) lines (e.g., Mg II) around quasars (Johnson et al 2018;Helton et al 2021;Johnson et al 2022;Dutta et al 2023;Epinat et al 2024;Liu et al 2024), galaxy groups (Epinat et al 2018;Chen et al 2019;Leclercq et al 2022;Dutta et al 2023;Epinat et al 2024), and galaxies with evidence of recent bursts of star formation (Rupke et al 2019;Burchett et al 2021;Zabl et al 2021). The joint morphological and kinematic analysis of the nebulae combined with deep galaxy surveys enabled by IFSs provide direct insights into the origins of the gas, including interactions, accretion, and outflows.…”
Section: Introductionmentioning
confidence: 99%